1981
DOI: 10.1007/bf01658307
|View full text |Cite
|
Sign up to set email alerts
|

Results of resection of carcinoma of the esophagus and cardia in 196 patients

Abstract: During the period 1962–1976, 196 patients were operated on for carcinoma of the esophagus (51) and cardia (145). In all patients resection with primary esophagogastrostomy or esophagojejunostomy was performed. Metastases involving the regional lymph nodes were found in 54.2% of patients. The early postoperative mortality rate was 21.9%. The most common cause of death was leakage at the esophagogastric anastomosis (46.5% of deaths). Mean survival period was 16.2 months, overall 5‐year survival rate was 18.7%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Adenocarcinomas of the gastric cardia and squamous cell carcinomas of the esophagus were mixed in several series [4][5][6][7][8][9][10][11][12][13][14][15] and should be reported separately because their natural behavior and prognosis are different. Carcinomas arising from the upper part in the stomach included in a previous report [16] were excluded in the present series, and, in every case, carcinoma was estimated to have arisen from the gastroesophageal junction.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinomas of the gastric cardia and squamous cell carcinomas of the esophagus were mixed in several series [4][5][6][7][8][9][10][11][12][13][14][15] and should be reported separately because their natural behavior and prognosis are different. Carcinomas arising from the upper part in the stomach included in a previous report [16] were excluded in the present series, and, in every case, carcinoma was estimated to have arisen from the gastroesophageal junction.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the 5 year-survival rate in stage III was 12% for Group 1 and 46% for Group 2 which usually underwent more radical operations including combined resections of the diaphragm and lymphadenectomy beyond the paraaortic lymph nodes (Hashimoto et al 1990). Orel et al (1981) reported the disrupted anastomosis and cardiorespiratory fairure accounted for most of the postoperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 45%
“…Anastomotic leakage has been reported to be the main postoperative complication and the main cause of death after surgery for tumors of the gastric cardia [13,18,19]. In this populationbased study there tended to be a higher frequency of anastomotic leakage than in some previous case series [19,20], but only 5 of 14 postoperative deaths after resective surgery could be partly or totally attributed to this complication.…”
Section: Discussionmentioning
confidence: 49%